Differential cross sections for positronium formation in positron-hydrogen scattering - Mohamed Kamali, M.Z.; Ratnavelu, K. (2007)
Positron scattering by hydrogen atom is interesting system to test theoretical methods due to its simplicity. Recently, theoretical calculations have reported differential cross sections (DCS) for positronium (Ps) formation for this system. The present work utilises coupled-channel optical method (CCOM) that allows simultaneous treatment of the target channels and the Ps channels in the close-coupling-method and the incorporation of the continuum effects via an optical potential to provide a comparative view of the DCS for Ps(1s) formation and Ps(2s) formation at energies ranging from 20 to 100eV. A large 12-states and 15-states CCOM calculations have been undertaken and the results compared with other available data.